If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 8) = 80 Reorder the terms: 3(8 + 4x) = 80 (8 * 3 + 4x * 3) = 80 (24 + 12x) = 80 Solving 24 + 12x = 80 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 12x = 80 + -24 Combine like terms: 24 + -24 = 0 0 + 12x = 80 + -24 12x = 80 + -24 Combine like terms: 80 + -24 = 56 12x = 56 Divide each side by '12'. x = 4.666666667 Simplifying x = 4.666666667
| -1.9r-9.3=15 | | 8n(6n+5)=7 | | 6.7=8.5-0.2x | | 4k+3v-10v-2k= | | 5+h=-3 | | 9y+270=10x | | 2(y+3)=4(y+5) | | -20g-20=-18g+16 | | 2x-1+7x=5 | | -3s+16=12s-14-18s | | 2x+5x-9=47 | | 3-2e=8-x | | 8x+3y+7y-2x= | | 21.64=4g+3.56 | | -18-19v=-16v | | -4x-3=12x-35 | | -8(x-7)=-48 | | -4u-7=4+7u | | 8+b=4 | | 6+7(x-7)=-5 | | -9(x-1)=-63 | | 7j-2=6j | | 29+7x=-4(7-7x)-6 | | 3=w*3-16 | | 7+6p=10p-9 | | -4(r+7)=-45 | | 11.72*x=16.6424 | | 6-k+2k=10-3k | | -q+9=2q | | 29+7x=-4(7-7x) | | 5x+11y+3=0 | | 10-d=-10+3d |